2020
DOI: 10.5146/tjpath.2020.01517
|View full text |Cite
|
Sign up to set email alerts
|

Primary myeloid sarcoma of ovary: a case report and review of the literature

Abstract: Myeloid sarcoma (granulocytic sarcoma or chloroma) is a tumor formed by myeloid precursor cells in any localization other than the bone marrow. It can occur without underlying acute myeloid leukemia (AML) or other myeloid neoplasms. Herein, we present a forty-two-year-old female patient who underwent surgery because of a left adnexal mass. Microscopic examination of the specimen revealed cord-like arrangement of the tumor cells with a diffuse growth of small blue cells effacing the ovarian stroma. Adult granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…4 Akyol et al described a 42 years old female patient with left ovarian myeloid sarcoma exhibiting positive immunoexpression with LCA, CD117, MPO, CD43, lysozyme, CD34, and CD68, in the absence of a history of leukemia. 8 Kahn et al presented a case of a 48 years old woman with MS involving the uterine corpus, fallopian tubes, and left ovary, after post-therapy clinical remission. 9 Ding et al also reported a 27 years old female, with a diagnosis of undifferentiated ovarian MS mass expressing focal CD45 and CD68 along with strong MPO and CD43 positive reaction.…”
Section: Discussionmentioning
confidence: 99%
“…4 Akyol et al described a 42 years old female patient with left ovarian myeloid sarcoma exhibiting positive immunoexpression with LCA, CD117, MPO, CD43, lysozyme, CD34, and CD68, in the absence of a history of leukemia. 8 Kahn et al presented a case of a 48 years old woman with MS involving the uterine corpus, fallopian tubes, and left ovary, after post-therapy clinical remission. 9 Ding et al also reported a 27 years old female, with a diagnosis of undifferentiated ovarian MS mass expressing focal CD45 and CD68 along with strong MPO and CD43 positive reaction.…”
Section: Discussionmentioning
confidence: 99%